Magnitude and factors associated with post-tuberculosis lung disease in low- and middle-income countries: A systematic review and meta-analysis - Elizabeth Maleche-Obimbo; Mercy Atieno Odhiambo; Lynette Njeri; Moses Mburu; Walter Jaoko; Fredrick Were; Stephen M. Graham (Public Library of Science (PLoS), 2022)
Background Emerging evidence suggests that after completion of treatment for tuberculosis (TB) a significant proportion of patients experience sequelae. However, there is limited synthesized evidence on this from low-income countries, from Sub-Saharan Africa, and in HIV infected individuals. We seek to provide an updated comprehensive systematic review and meta-analysis on the magnitude and factors associated with post-TB lung disease (PTLD) in low- and middle-income countries (LMICs). Methods We searched PubMed, Embase and CINAHL for studies from LMICs with data on post-TB lung health in patients who had previously completed treatment for pulmonary TB. Data on study characteristics, prevalence of PTLD-specifically abnormal lung function (spirometry), persisting respiratory symptoms and radiologic abnormalities were abstracted. Statistical analysis was performed using Microsoft Excel and R version 4.1 software, and random effects meta-analysis conducted to compute pooled prevalence of PTLD, evaluate heterogeneity, and assess factors associated with PTLD. Results We identified 32 eligible studies with 6225 participants. Twenty-one studies were from Africa, 16 included HIV infected participants, spirometry was conducted in 20 studies, symptom assessment in 16 and chest imaging in eight. Pooled prevalence of abnormal lung function was 46.7%, persistent respiratory symptoms 41.0%, and radiologic abnormalities 64.6%. Magnitude of any type of PTLD varied by HIV status (HIV- 66.9%, HIV+ 32.8%, p = 0.0013), across geographic setting (SE Asia 57.5%, Southern America 50.8%, and Africa 38.2%, p = 0.0118), and across urban-rural settings (symptom prevalence: rural 68.8%, urban 39.1%, mixed settings 27.9%, p = 0.0035), but not by income settings, sex or age-group. Conclusions There is high burden of post-TB persistent respiratory symptoms, functional lung impairment and radiologic structural abnormalities in individuals living in LMICs. Burden varies across settings and by HIV status. This evidence may be valuable to advocate for and inform implementation of structured health care specific to the needs of this vulnerable population of individuals.